Impact of Sustainable Structural Systems Undergraduate Research on Education and Program Development at MSU Denver. Issue 1762 (16th February 2015) - Balogh, Jeno; Haynes, Sandra; Brown, Aaron
ABSTRACT: This paper presents the impact of three undergraduate research projects focusing on constructability assessment of adhesive-based wood-concrete composite structural members, on a solar heating technology that can be utilized in conjunction with this system and how these projects relate to engineering education and program development at Metropolitan State University of Denver (MSU Denver). The sustainable structures topic was pursued within senior project classes offered in summer 2013 and 2014 at MSU Denver. The first project addressed new members, while the second dealt with retrofits. These projects were motivated by faculty research in developing new sustainable construction systems using composites. Since underlining faculty research is on an international scale, students had direct access to researchers world-wide. Such research was used as an instrument in the "Experimental Methods in Structural Engineering" course. The students were also exposed to a broader-range of diverse ideas within the field of research by attending an international conference on timber bridges. The solar furnace project was run in parallel, providing students an opportunity to conduct research targeted at design and performance optimization of the heating units with the intention to assess the benefits of incorporating these devices into future buildings using the sustainable structural system technology. Experiences gained through the undergraduate research activities were applied in the design of a proposed Sustainable Systems Engineering degree program.